IMPROVEMENT OF THE SCIENTIFIC PEDAGOGICAL INNOVATIVE EDUCATION SYSTEM IN THE FIELD OF SPORTS (American Journal of Interdisciplinary Research and Development, 2026)
This article reflects the main aspects of organizing innovative educational activities in the training of qualified, mature professional scientific and pedagogical specialists who meet modern requirements, possessing skills formed on the basis of education, upbringing, and scientific research in the field of sports.